EFEKTIVITAS PELAKSANAAN KEGIATAN BELAJAR DARI RUMAH (BDR) PADA SISWA SD DI KOTA SAMARINDA - Siska Oktaviani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Various cities in Indonesia, Samarinda are one of the cities experiencing the impact of this pandemic. In education itself, the city of Samarinda has followed the government's direction since March 2020 to prevent the spread of COVID-19 by conducting learning from home (BDR) activities. The purpose of this study was to describe the information obtained regarding the effectiveness of implementing learning from home (BDR) activities for elementary school students in the city of Samarinda during the Covid-19 pandemic. This study uses a qualitative descriptive research method. This research will be conducted at SDN 012 Samarinda Ulu, Samarinda city in the even semester from April to July 2021. The subjects of this research are students of SDN 012 Samarinda Ulu who are the main informants. As a triangulation researcher added informants, namely class teachers and parents of students from SDN 012 Samarinda Ulu. To obtain the data that will be needed in this study, it is carried out by techniques, namely interviews and documentation. Activities in analyzing the data obtained are by means of data reduction, data display and conclusion drawing/verification. To test the validity of the data in this study, triagulation is used, namely source triagulation. The results of this study can be concluded that one form of preventing the spread of covid-19 is by conducting learning from home (BDR) activities, in Samarinda City itself, especially at the elementary school level, the process of implementing BDR is carried out online. The steps for implementing online BDR are started from the classroom teacher by asking the virtual attendance of students. After that, it was continued with the delivery of material, then giving assignments and collecting assignments from students. The dominant media used in online learning is mobile phones or smartphones. Furthermore, BDR constraints include student saturation, giving a lot of assignments, difficulty understanding the material and internet network disturbances.